Referendum design, quorum rules and turnout - Conraria, Luís Aguiar (2014)
In this article, we focus on the consequences of quorum requirements for turnout in referendums. We use a rational choice, decision theoretic voting model to demonstrate that participation quorums change the incentives some electors face, inducing those who oppose changes in the status quo and expect to be in the minority to abstain. As a result, paradoxically, participation quorums decrease electoral participation. We test our model’s predictions using data for all referendums held in current European Union countries from 1970 until 2007, and show that the existence of a participation quorums increases abstention by more than ten percentage points.